2018
DOI: 10.1063/1.5023400
|View full text |Cite
|
Sign up to set email alerts
|

First measurements of remaining shell areal density on the OMEGA laser using the Diagnostic for Areal Density (DAD)

Abstract: A glass Cherenkov detector, called the Diagnostic for Areal Density (DAD), has been built and implemented at the OMEGA laser facility for measuring fusion gammas above 430 keV, from which remaining shell ⟨⟩ can be determined. A proof-of-principle experiment is discussed, where signals from a surrogate gas Cherenkov detector are compared with reported values from the wedge range filter and charged particle spectrometer and found to correlate strongly. The design of the more compact port-based DAD diagnostic and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
4
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(4 citation statements)
references
References 17 publications
0
4
0
Order By: Relevance
“…The gamma system is designed to record 4.4 MeV gammas from the 12 C(n,n ′ γ) 12 C reaction between 14.1 MeV primary neutrons and the remaining high-density carbon (HDC) ablator, which has a strength of 1.1×10 −5 γ/mg/cm 2 /neutron. [16][17][18] There will be an additional signature from the DT gamma, [19][20][21] which is emitted with a strength of (4.6 ± 0.6) ×10 −5 per fusion neutron; however, remaining shell levels at NIF during ICF experiments are in the region of 400 mg/cm 2 , therefore approximately 100× more carbon gammas interact with the scintillator during typical experiments. Original investigations 22 suggested that LYSO would be the ideal candidate for a gamma imaging system at NIF, however, the scintillator could not be manufactured in a large enough single piece (approx.…”
Section: The Nif Nuclear Imaging Systemmentioning
confidence: 99%
“…The gamma system is designed to record 4.4 MeV gammas from the 12 C(n,n ′ γ) 12 C reaction between 14.1 MeV primary neutrons and the remaining high-density carbon (HDC) ablator, which has a strength of 1.1×10 −5 γ/mg/cm 2 /neutron. [16][17][18] There will be an additional signature from the DT gamma, [19][20][21] which is emitted with a strength of (4.6 ± 0.6) ×10 −5 per fusion neutron; however, remaining shell levels at NIF during ICF experiments are in the region of 400 mg/cm 2 , therefore approximately 100× more carbon gammas interact with the scintillator during typical experiments. Original investigations 22 suggested that LYSO would be the ideal candidate for a gamma imaging system at NIF, however, the scintillator could not be manufactured in a large enough single piece (approx.…”
Section: The Nif Nuclear Imaging Systemmentioning
confidence: 99%
“…The main detectors that are currently in use at ICF facilities and may be used for nuclear astrophysics experiments such as cross-section or S-factor measurements include the two Gas Cherenkov Detectors (GCD's) GCD-1 [10,11] and GCD-3 [12] as well as the Diagnostic for Areal Density (DAD) [13]. There are GCD's available at both the NIF and OMEGA, however, the DAD is only available at OMEGA.…”
Section: Detectors and Calibrationmentioning
confidence: 99%
“…It is available at OMEGA only. It was originally deployed in 2014 to measure remaining shell areal densities via measurement of 4.4-MeV gammas from the first excited state of carbon [13], but is capable of measuring any gammas above ~0.34 MeV (assuming the standard index of refraction n = 1.46 for fused silica). The DAD consists of 6 mm of tungsten shielding in front of a 6.39-cm diameter, 5-cm thick piece of fused silica, which is directly coupled to a PMT.…”
Section: Figurementioning
confidence: 99%
See 1 more Smart Citation